#### Question

If `(x^2 + 3xy^2)/(3x^2y + y^3) = (m^2 + 3mn^2)/(3m^2n + n^3)` show that nx = my

#### Solution

`(x^2 + 3xy^2)/(3x^2y + y^3) = (m^2 + 3mn^2)/(3m^2n + n^3)`

Applying componendo and dividendo

`(x^3 + 3xy^2 + 3x^2y + y^3)/(x^3 + 3xy^2 - 3x^2y - y^3) = (m^3 + 3mn^2 + 3m^2n + n^3)/(m^3 + 3mn^2 - 3m^2n - n^3)`

`(x + y)^3/(x - y)^3 = (m + n)^3/(m - n)^3`

`(x + y)/(x - y) = (m + n)/(m - n)`

Applying componendo and dividendo

`(x + y + x - y)/(x + y - x + y) = (m + n + m - n)/(m + n - m + n)`

`(2x)/(2y) = (2m)/(2n)`

`x/y = m/n`

nx = my

Is there an error in this question or solution?

Advertisement

Advertisement

If `(X^2 + 3xy^2)/(3x^2y + Y^3) = (M^2 + 3mn^2)/(3m^2 + N^3)` Show that Nx = My Concept: Componendo and Dividendo Properties.

Advertisement